Th17 expression and IL-17 levels in laryngeal squamous cell carcinoma patients. (3rd May 2016) - Li, Fu-Jun; Cai, Zhi-Jian; Yang, Fei; Zhang, Shou-De; Chen, Ming
ABSTRACT: Conclusion The Th17 cell frequency in peripheral blood and levels of IL-17 showed significant differences between patients with laryngeal squamous cell carcinoma and those with vocal cords polyps. Serum levels of IL-17 were correlated with laryngocarcinoma staging.Objectives To investigate associations among the frequency of Th17 cells, levels of IL-17, and laryngeal squamous cell carcinoma.Method Eighty in-patients with laryngeal squamous cell carcinoma and 114 in-patients with polypus of the vocal cord were enrolled. Th17 cell frequencies in peripheral blood and serum levels of IL-17 were measured by flow cytometry and enzyme-linked immunosorbent assay, respectively. The tissue expression levels of IL-17 mRNA transcripts and protein were measured using quantitative RT-PCR or immunohistochemical detection, respectively.Results Th17 cell frequencies in peripheral blood and serum concentrations of IL-17 were significantly higher in patients with laryngocarcinoma compared with those in patients with polyps ( p < 0.01 for both Th17 cells and IL-17 levels). Serum concentrations of IL-17 were significantly higher in patients with advanced laryngocarcinoma than in patients with early laryngocarcinoma ( p < 0.01). The mRNA and protein levels of IL-17 were significantly higher in laryngocarcinoma tissues than in adjacent normal tissues ( p < 0.01 for mRNA levels, p < 0.05 for protein levels).